DIFFERENTIAL DIAGNOSIS PERIPHERAL OSTEOBLASTOCLASTOMA AND EPULID - V.V. Lepsky (Український стоматологічний альманах)
Among the primory tumours of osteoclastoma’s lower jaw comprise 65 % - central located – 17%, peripheral – 18% (so called giant cell epulis).